McGraw-Hill concise encyclopedia of bioscience. (New York : McGraw-Hill, 2005)
Hundreds of articles explore the most important fields of science. Based on content from the McGraw-Hill Concise Encyclopedia of Science & Technology, Fifth Edition, each of these subject-specific quick-reference guides features: Detailed, well-illustrated explanations; Hundreds of concise articles in each volume; An easy-to-understand presentation, accessible and interesting to non-specialists; A portable, convenient format; Bibliographies, appendices, and other information supplement the articles.
Articles, A-Z -- Appendix. Bibliographies ; Equivalents of commonly used units for the U.S. Customary System and the metric system ; Conversion factors for the U.S. Customary System, metric system, and International System ; ABO blood group system ; Amino acid abbreviations ; Universal (standard) genetic code ; Some functions of essential vitamins ; Major groups of viruses ; Cranial nerves of vertebrates ; Classification of living organisms ; Biographical listing.
Includes bibliographical references (p. 885-897) and index.
Keywords: Biology -- Encyclopedias; Biologie; Biologie; Sciences biologiques; 2